Phenological patterns and sampling decision rules for arthropods in cotton fields in Paraná, Brazil: before boll weevil - Pizzamiglio, Marina Ângela; Gutierrez, Andrew Paul; dos Santos, Walter J.; Gallagher, K. D.; de Oliveira, Wagner S.; Fujita, Zuleika H. (Pesquisa Agropecuaria Brasileira, 2014)
Several species of arthropods commonly found in untreated cotton ia Paraná, Brazil, were sampled using the accurate whole plant bag sampling method (WPBS). 'Ibe data provide important background information for cotton prior to lhe expected increase in insecticide use for the control of the newly introduced cotton boil weevil (Anthonomus grandis Boh.) in Paraná, Brazil. Decision sampling rules base on Taylor's power law were developed for many of the common species. The relationship between the proportion of infested plants and the average density of arthropods per plant for cotton aphid and the cotton stem borer were assessed for the cotton aphid (Aphis gossypii Glover, 1876) and the stem borer (Eutinobothrus brasiliensis (Hambieton, 1937)). These functions may be used in the field to estimate the mean density of these pests in the field from presence-absence observations.